Effective police leadership in the 21st century : new paradigms for a novel context - Elkington, Rob; O'Conner, Christopher D.; Castell, Tiffany; Sylven, Les (Emerald Publishing Limited, 2025)
The need for effective leadership in policing is quite evident, given the range of accounts of Police officers and Police organizations failing to serve the public with professionalism and integrity. Effective Police Leadership in the 21st Century: New Paradigms for a Novel Context is a first-of-its-kind publication that includes an interdisciplinary and international framework focused on Police leadership in the 21st century. The book features case studies from real-world Police leadership situations. This book provides a platform and pathway to equip existing and emerging police leaders with a range of leadership mindsets and skillsets. The integration of real-world case studies on former and current Police leaders further supports critical interaction and reflection for the readers.